Analisis Liabilitas dan Ekuitas terhadap Laba pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia - Aprilia, Riska; Ramadhani, Aulya Marshanda; Labibah, Bintu; Nurahma, Salsa; Maesaroh, Syti Sarah (Jurnal Riset AKuntansi dan Bisnis, 2024)
Primary consumer goods sector companies play an important role in the economy because they mainly fulfill basic human needs to improve the quality of life. This research is motivated by the decline in profits in several companies in the sector in recent years which has become a concern for researchers. Data analysis uses multiple regression analysis through a quantitative descriptive approach. The company sample consists of primary consumer sector companies listed on the IDX in 2020-2022. The observed variables include total liabilities, equity, and profits of related companies. Hypothesis testing is carried out to determine the effect of the independent variable on the dependent variable. The results show that liabilities and equity simultaneously have a significant positive effect on company profits. However, partially, one of the research variables, namely equity, does not meet the significance requirements so that it can be interpreted that there is no influence between equity on profit growth. This indicates that between liabilities and equity that have a significant influence on profit growth are liabilities. Therefore, it is necessary to add other factors to get a higher coefficient of determination.